2016
DOI: 10.1039/c6ra19790f
|View full text |Cite
|
Sign up to set email alerts
|

Flow trifluoromethylation of carbonyl compounds by Ruppert–Prakash reagent and its application for pharmaceuticals, efavirenz and HSD-016

Abstract: Flow trifluoromethylation of carbonyl compounds using the Ruppert–Prakash reagent, Me3SiCF3 is disclosed including enantioselective trifluoromethylation. Synthesis of pharmaceuticals, efavirenz and HSD-016 were achieved by this flow method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“… 14 Mechanism II has been extensively adopted in the design and interpretation of asymmetric trifluoromethylation. 16 , 29 , 31 …”
Section: Resultsmentioning
confidence: 99%
“… 14 Mechanism II has been extensively adopted in the design and interpretation of asymmetric trifluoromethylation. 16 , 29 , 31 …”
Section: Resultsmentioning
confidence: 99%
“…The presence of HMDS could then cause the decomplexation of the polymeric THF-solvate. The real-time 19 F NMR monitoring provided important information concerning the reaction progress under the conditions described in Table 1 - Table 1, entry 5). Also the hypothesis of a progressive cleavage of the trimethylsilyl group from 4a was taken into account, whereby the fluoride anion, derived hypothetically from the decomposition of the trifluoromethanide anion, would be responsible.…”
Section: Resultsmentioning
confidence: 99%
“…67,68 The reaction conditions were accurately investigated, taking advantage of the real-time monitoring of the reaction mixture. It was found that a lower temperature (-40 °C) and longer residence time (57 minutes The reaction was continuously monitored by FT-IR (Figure 5c) and by 19 F NMR (Figure 5d), discovering that an excess of chlorotriethylsilane (Et 3 SiCl, 2M), used as electrophile, was crucial to suppress the formation of triethylsilyl fluoride (Et 3 SiF; signal at -151.02 ppm in the 19 F NMR spectrum) as by-product. Under these reaction conditions, full consumption of CF 3 H was observed (Figure 5c, blue line, trend of the peak at 1132 cm -1 ; Figure 5d, disappearance of the doublet at -79.49 ppm) and clean formation of compound 8 was detected (Figure 5d, green line, trend of the peak at 1251 cm -1 ; Figure 5d, appearance of the singlet at -61.44 ppm).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…upon treatment of activators. Bases such as the fluoride ion, metal alkoxides, hydroxides, acetates, carbonates, phosphates, amines, amine oxides, phosphines, or N ‐heterocyclic carbenes can activate Me 3 Si‐CF 3 and nucleophilic trifluoromethylation proceeds very smoothly under mild conditions . Acids, which activate carbonyl compounds, are also effective for nucleophilic trifluoromethylation ,.…”
Section: Methodsmentioning
confidence: 99%